Islamic elements in the art of Malay tradisional court letter-writing - Ahmat Adam (Universiti Malaysia Sabah, 1997)
Traditional Malay letter-writing is an ancient art that is no longer pursued. It was, nevertheless, an art that became increasingly important in Malay diplomacy since the time of the Melaka sultanate in the fifteenth century until the closing of the nineteenth century. During the period of the Melaka sultanate letters that were received from or sent to foreign rulers were accorded special treatment. The Sejarah. Melayu (Malay Annals) mentioned that when the letter from the emperor of China arrived at the port of Melaka during the reign of Sultan Mansur Syah, the letter was received with pomp and grandeur. It was conveyed in a procession from the port to the palace where the sultan sat in audience and upon arrival was read aloud to the sultan by the khatib (the mosque official in charge of delivering the Friday sermon).